Social skills required for the social worker to work with criminals from the point of view of the counselors - برقاوي, هناء (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research aimed to identify the social skills that must be available for the social counselor to work with perpetrators of the criminal act from the counselors' point of view, and to measure the differences between the average scores of the research sample members' answers in the questionnaire of the social skills that must be available for the social counselor's work according to the variables: (gender, educational qualification). The descriptive analytical approach was relied upon. The research sample amounted to (47) social counselors from the social counselors working in the Good Monk Association in the capital, Damascus, and the Aftercare Center affiliated with the Prisoners' Care Association and their Families in the city of Aleppo. The questionnaire of the social skills that must be available for the social counselor to work with perpetrators of the criminal act from the counselors' point of view was applied to them, and it includes (76) items. The research concluded with the following results: The research sample members confirmed the need for counselors to have the social skills that must be available for their work with perpetrators of the criminal act to a high degree on the total score of the questionnaire, as the ordinal mean value reached (3.88). There is no statistically significant difference between the average scores of the research sample members on the questionnaire of social skills required for the work of a social counselor according to the gender variable, and there are statistically significant differences according to the educational qualification variable in favor of social counselors with an educational qualification (diploma or higher).